Biological maturity vs. relative age: Independent impact on physical performance in male and female youth handball players - Alfonso de la Rubia; Adam Leight Kelly; Jorge García-González; Jorge Lorenzo; Daniel Mon-López; Sergio Maroto-Izquierdo (Termedia Publishing House, 2023)
Maturity status and relative age are two of the determining factors in talent development. The aim of the study was to analyze the influence of biological maturity status and relative age on physical performance in young male and female handball players. The sample included 48 males (14.11±1.17 years) and 41 females (14.25±1.64 years) players from one Spanish professional handball academy. Anthropometric data (height, sitting height, body mass and self-reported biological parent heights) and physical performance data (CMJ, DJ, 20 m speed, T-test and throwing velocity) were collected. Biological maturity status was determined as the percentage of predicted adult height, while relative age was estimated in birth quartiles based on biennial age grouping (Q1-Q8). The results showed a positive correlation between maturity status and CMJ in male players ( p < 0.01). Differences in CMJ performance according to maturity status were identified ( p < 0.05), with higher jump heights being recorded especially in early maturing boys ( p < 0.01) and first lines and wings ( p < 0.05). The variance in CMJ test scores could be explained by the maturity status by 42.90% in U-15 ( p < 0.05) and 72.60% in U-16 male players ( p < 0.001). By contrast, no differences were found in girls ( p > 0.05). Moreover, no relationships were found between relative age and indices of physical performance ( p > 0.05). Overall, maturity status had greater impacts on the tests of physical performance than relative age. Stakeholders should monitor the maturity status of young handball players to avoid physical performance biases that do not allow them to develop their sporting potential.